Improving The Child-Centered Learning Process in Preschool Education - Norkulova Mamura Husniddin qizi (Genius Journals, 2022)
The main purpose of pedagogical education is to ensure the mental, spiritual, moral, aesthetic, physical development of the individual, to reveal his creative potential, to create the necessary conditions for the formation of humane relations. It is hoped that skilled educators will be able to demonstrate the child's talents in this way and will be effective in perfecting the lessons. The processes in the development centers established in all age groups of preschool education organizations are considered to help children to constantly acquire and consolidate new knowledge.
Keywords: Preschool education; pedagogical education; person-centered education; physical development